Teaching Essay Writing to EFL Students Using WTL (Write To Learn (WTL) Digital Tool - Yogi Widiawati; Ardina Askum (Politeknik Negeri Bali, 2020)
A myriad research has demonstrated the use of digital tool as an approach to teaching of English as a foreign language (EFL), but little research on this topic of interest has been undertaken in the Indonesian secondary school and higher education context. Particularly, the use of digital tool as practicing and examining students’ writing remains under-explored in this educational setting. With these in mind, this research presents an empirical study that looks into to what extent the deployment of a digital tool mediates multimodal learning tasks in the EAL classroom. The study specifically examines challenges and benefits of using the digital tool “write to learn” to develop students’ writing and reading competences. The study also looks at the roles of teacher and students in the entire learning process. A total of 80 polytechnic students volunteered to participate the study. Individually, they were assigned to perform a series of tasks, including (1) connecting to “write to learn” website, (2) reading articles and instruction in, and (3) writing essays. Empirical data were garnered from postings, students’ writing and students’ interviews. Drawing on these data, the present chapter reports on four major findings, that is: (1) drafting and negotiating strategies for writing essay creation, (2) framing the use of language in composing, (3) discussing the result essay creation and improvement, and (4) positioning roles of teachers and students in the entire learning process.